2020
DOI: 10.1111/cen.14368
|View full text |Cite
|
Sign up to set email alerts
|

Iodine status in UK–An accidental public health triumph gone sour

Abstract: The improvement in iodine status among the UK population from the 1930s onwards has been described as an ‘accidental public health triumph’ despite the lack of any iodine fortification program. However, iodine deficiency in the UK has re‐emerged in vulnerable groups and is likely due to a combination of changing farming practices, dietary preferences and public health priorities. The UK is now among only a minority of European countries with no legislative framework for iodine fortification. The experience of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 53 publications
(65 reference statements)
0
19
0
Order By: Relevance
“…For example, a survey of primary school age children in the west of NI showed iodine sufficiency [ 7 ]. Potential causes for the re-emergence of iodine deficiency include changing farming techniques and dietary habits around dairy consumption in at least some age groups [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, a survey of primary school age children in the west of NI showed iodine sufficiency [ 7 ]. Potential causes for the re-emergence of iodine deficiency include changing farming techniques and dietary habits around dairy consumption in at least some age groups [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…A study of pregnant women from the same Belfast centre showed iodine deficiency, with a median UIC below the WHO recommended cut-off in pregnancy (150 μg/l), despite 55 % of participants reporting taking a supplement containing iodine (23) . This highlights the vulnerability of pregnant populations to iodine deficiency, particularly in the recently demonstrated precarious setting of low-level sufficiency as observed in the school-age population in the UK (24) . Improving awareness of this issue via public health campaigns targeting vulnerable groups may play an important role in improving iodine nutrition, along with consideration of fortification, supplementation during pregnancy and lactation, and midwife education (25) .…”
Section: Introductionmentioning
confidence: 78%
“…In children, 70% of those aged 1.5–10 years are estimated to consume fish, whereas only 50% of 11–18 year olds are consumers with males (~55%) consuming more than their female counterparts (~45%). It is this latter cohort of women entering into reproductive age together with pregnant individuals that are generally identified as being more at risk of iodine deficiencies owing to the problems it poses to foetal and neonatal development [ 4 , 5 , 11 , 12 , 13 , 14 ]. However, calculation of seafood intakes from NDNS disaggregated seafood data (years 1–8 combined) indicates that this age group (11–18) consumes the most fish of all UK age groups (36.3 g·day −1 ), equivalent to 90.8% of the minimum 280 g recommended intake based on two servings of 140 g [ 28 ], although females still consume less than their male counterparts (34.2 and 38.5 g·day −1 or 85.5 and 96.3%, respectively) ( Table 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…These allowances are mostly expected to be satisfied through dietary consumption. Nevertheless, in the UK, as well as Western Europe in general, there is some concern that iodine intake has become mild to moderately inadequate, especially among more vulnerable groups such as young children and women of reproductive age, despite improvements in nutrition [ 4 , 5 , 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%